2015
DOI: 10.1007/s10661-015-4447-0
|View full text |Cite
|
Sign up to set email alerts
|

Occupants’ satisfaction toward building environmental quality: structural equation modeling approach

Abstract: It is accepted that occupants who are more satisfied with their workplace's building internal environment are more productive. The main objective of the study was to measure the occupants' level of satisfaction and the perceived importance of the design or refurbishment on office conditions. The study also attempted to determine the factors affecting the occupants' satisfaction with their building or office conditions. Post-occupancy evaluations were conducted using a structured questionnaire developed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…Few studies have linked BIM with POE, notably the work of Göçer et al [3,9] who created a GIS and BIM-enabled platform to support bi-directional communication between FM teams and users and created a series of supporting BIM visualizations of POE survey results. This paper responds to existing research gap of POE integration within BIM [5] and presents strategies for leveraging maintenance work orders to enhance and complement POEs. An FM-BIM integration approach is integral to implementation, providing an information management framework and visualization capacity.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Few studies have linked BIM with POE, notably the work of Göçer et al [3,9] who created a GIS and BIM-enabled platform to support bi-directional communication between FM teams and users and created a series of supporting BIM visualizations of POE survey results. This paper responds to existing research gap of POE integration within BIM [5] and presents strategies for leveraging maintenance work orders to enhance and complement POEs. An FM-BIM integration approach is integral to implementation, providing an information management framework and visualization capacity.…”
Section: Introductionmentioning
confidence: 92%
“…The first three are best defined by the presence of alarms, incident reports, and security system information, which can all be integrated in an FM-BIM, but this is beyond the scope of this initial study. Acoustic, thermal, visual, and indoor air quality [5] define the indoor environmental quality (IEQ) of a space and address the latter two categories while reports of broken fixtures, furniture and equipment (FFE) and custodial and groundskeeping requests indicate compromised functionality and condition issues (covering both maintenance and cleanliness) of specific elements within the space.…”
Section: Information Required To Support Poesmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to be adaptive to stress has dire consequences at individual and organizational levels [2]. Studies have shown that SBS and stress not only has an impact on productivity [3] [4], but also on job satisfaction [5] [6] and other organizational outcomes. In a nutshell, SBS and stress have a prevalent influence on organizational effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Tharim et al identified the link between IEQ, occupants' satisfaction and productivity in GBI rated office Building based on PLS-SEM [25]. Kamaruzzaman et al applied the SEM approach to determine which indoor environmental factor had the most significant impact on occupants' satisfaction [26]. Finell et al explored whether indoor air problems observed in schools associated with students' perceptions of the teacher-student relationship and class spirit [27].The purpose of this paper, therefore, is to identify the combined effects of indoor air quality and socioeconomic factors on health based on structural equation modeling, using the field measurement data in Northeast China.…”
mentioning
confidence: 99%